1978
DOI: 10.1056/nejm197807062990103
|View full text |Cite
|
Sign up to set email alerts
|

Gynecomastia and Gonadal Dysfunction in Adolescent Boys Treated with Combination Chemotherapy for Hodgkin's Disease

Abstract: We studied 19 Ugandan boys with Hodgkin's disease who had been treated with mechlorethamine, vincristine, procarbazine and prednisone and who survived at least two years to assess testicular germ-cell depletion in pubescent boys on combination chemotherapy, as had previously been demonstrated in sexually mature men. Nine of 13 pubertal boys (ages 11 to 16) had moderate to severe gynecomastia and germinal aplasia, a 10-fold increase in mean (+/- S.D.) serum follicle-stimulating hormone (34.8 +/- 20.5 mlU per mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(58 citation statements)
references
References 33 publications
4
51
1
2
Order By: Relevance
“…None of the patients had gynaecomastia unlike the boys in Sherins study (Sherins et al, 1978). However, 16/28 treated with chemotherapy and 2/5 treated with radiotherapy alone (inverted Y 3,500 cGy) have elevated serum LH levels, first noted 5-19 years from diagnosis.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…None of the patients had gynaecomastia unlike the boys in Sherins study (Sherins et al, 1978). However, 16/28 treated with chemotherapy and 2/5 treated with radiotherapy alone (inverted Y 3,500 cGy) have elevated serum LH levels, first noted 5-19 years from diagnosis.…”
Section: Discussionmentioning
confidence: 72%
“…Infertility appears to be almost inevitable in adult males with Hodgkin's disease treated by six or more courses of MOPP or MVPP (mustine, vincristine/vinblastine, procarbazine, prednisolone) (Whitehead et al, 1982a). Chemotherapy induced testicular damage in patients treated for Hodgkin's disease in childhood was first reported by Sherins et al, in 1978. Whitehead et al (1982b reported 15 males treated with MOPP for Hodgkin's disease in childhood and concluded that severe testicular damage is common, with azoospermia, but normal pubertal development.…”
mentioning
confidence: 99%
“…Гистологические исследования образцов тестику-лярной ткани подростков, получавших лечение в пре-пубертатный и пубертатный периоды, выявили апла-зию герминативного эпителия [41,42]. В работе E. Puscheck et al [43] показано, что, несмотря на нор-мальный уровень половых гормонов (ЛГ, ФСГ, тесто-стерон), в ткани яичка определяются структурные изменения (интерстициальный фиброз и поврежде-ние семявыносящих канальцев), характерные для тя-желых токсических повреждений.…”
Section: гонадотоксичность противоопухолевой терапии у подростковunclassified
“…Patients with stage III and stage IV HD received mechlorethamine, vincristine, procarbazine, and prednisone (MOPP) in combination with irradiation. The occurrence of severe sequelae, including a diminished growth of soft tissue and bone, aseptic bone necrosis [1], hypothyroidism [2], gonadal dysfunction [3,4] and secondary malignancies [5,6] stimulated us to search for other treatment regimens. In 1975 we changed our policy.…”
Section: Introductionmentioning
confidence: 99%